Efficient Delivery of SARS-CoV-2 Plasmid DNA in HEK-293T Cells Using Chitosan Nanoparticles - Citlali Cecilia Mendoza-Guevara; Alejandro Martinez-Escobar; María del Pilar Ramos-Godínez; José Esteban Muñoz-Medina; Eva Ramon-Gallegos (Pharmaceuticals)
Background/Objectives: Gene therapy has emerged as a promising strategy for treating a wide range of diseases. However, a major challenge remains in developing efficient and safe delivery systems for genetic material. Nanoparticles, particularly chitosan nanoparticles (CNPs), have gained significant attention as a potential solution. This study focuses on designing a SARS-CoV-2 plasmid DNA (pDNA) conjugated with CNPs and evaluating its in vitro delivery efficiency. Methods: The Omicron Spike DNA sequence was inserted into the pIRES2-eGFP expression vector, and CNPs were synthesized with optimized physicochemical properties to enhance stability, cellular uptake, and transfection efficiency. The conjugate was characterized using UV-Vis, FT-IR, DLS, and TEM techniques. Transfection efficiency was assessed and compared to the commercially available TurboFect reagent as a control. Results: CNPs-pDNA polyplexes with an average size of 159.0 ± 33.1 nm (TEM), a zeta potential of +19.7 ± 0.3 mV, and 100% ± 0.0 encapsulation efficiency were developed as a non-viral delivery system. CNPs efficiently serve as a delivery vehicle for the constructed pDNA without altering cell morphology, achieving transfection efficiencies of 62–74%, compared to 55–70% for TurboFect. Furthermore, RT-qPCR confirmed the expression of Spike mRNA, and Western blot assays validated the expression of Spike protein. Notably, Spike protein expression from CNPs was found to be two-fold higher than the control at 96 h post-transfection. Conclusions: These findings suggest that CNPs are a promising and versatile platform for delivering genetic material. Importantly, this study highlights the intrinsic properties of chitosan, without the use of additional ligands, as a key factor in achieving efficient gene delivery.